Towards electronic learning features in education 4.0 environment: literature study - Nor Azah Mansor; Natrah Abdullah; Hayati Abd Rahman (Institute of Advanced Engineering and Science, 2020)
This paper presents electronic learning features in Education 4.0 environment. Malaysian government encourages Higher Education Institution (HEIs) to embed technologies in order to prepare future education (Education 4.0). Besides, developing skills among students is important to be more adaptable in changing the environment. Current HEIs using Learning Management System (LMS) has lack of interactive features and non-personalized learning. Therefore, this article set out to analyze the existing literature on e-learning practices in Education 4.0 and to propose e-learning features suits in Education 4.0 environment. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, a systematic review of the Scopus 24 related studies. Further review of these articles resulted in seven principles of e-learning features based on the constructivism principle – Self-regulation, Personal perspective, Experiential learning, Social learning, Learning Community, Creating and Sharing Knowledge, Structure and layout which can be used to upgraded and redesigned LMS.